2020
DOI: 10.1093/nar/gkaa162
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of genetic variation in transcription factors and its implications for the evolution of regulatory networks in Bacteria

Abstract: The evolution of regulatory networks in Bacteria has largely been explained at macroevolutionary scales through lateral gene transfer and gene duplication. Transcription factors (TF) have been found to be less conserved across species than their target genes (TG). This would be expected if TFs accumulate mutations faster than TGs. This hypothesis is supported by several lab evolution studies which found TFs, especially global regulators, to be frequently mutated. Despite these studies, the contribution of poin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…This reflects general features of M. tb’s regulatory network, which exhibits a high degree of connectivity between regulatory pathways ( Chauhan et al, 2016 ; Galagan et al, 2013 ) as well as a hierarchical structure in which master regulators can rapidly calibrate global patterns of gene expression ( Chauhan et al, 2016 ; Parvati Sai Arun et al, 2018 ). Similar findings have also been obtained in other systems, where experimentally evolved populations have shown adaptation in TFs and other global regulators, with global impacts on gene expression ( Ali and Seshasayee, 2020 ; Conrad et al, 2010 ; Philippe et al, 2007 ; Rodríguez-Verdugo et al, 2016 ; Saxer et al, 2014 ). These mutations occur quickly to enable rapid adaptation to new environments, and it is hypothesized that secondary selection may act to refine gene expression after the initial burst of adaptation ( Ali and Seshasayee, 2020 ; Rodríguez-Verdugo et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This reflects general features of M. tb’s regulatory network, which exhibits a high degree of connectivity between regulatory pathways ( Chauhan et al, 2016 ; Galagan et al, 2013 ) as well as a hierarchical structure in which master regulators can rapidly calibrate global patterns of gene expression ( Chauhan et al, 2016 ; Parvati Sai Arun et al, 2018 ). Similar findings have also been obtained in other systems, where experimentally evolved populations have shown adaptation in TFs and other global regulators, with global impacts on gene expression ( Ali and Seshasayee, 2020 ; Conrad et al, 2010 ; Philippe et al, 2007 ; Rodríguez-Verdugo et al, 2016 ; Saxer et al, 2014 ). These mutations occur quickly to enable rapid adaptation to new environments, and it is hypothesized that secondary selection may act to refine gene expression after the initial burst of adaptation ( Ali and Seshasayee, 2020 ; Rodríguez-Verdugo et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings have also been obtained in other systems, where experimentally evolved populations have shown adaptation in TFs and other global regulators, with global impacts on gene expression ( Ali and Seshasayee, 2020 ; Conrad et al, 2010 ; Philippe et al, 2007 ; Rodríguez-Verdugo et al, 2016 ; Saxer et al, 2014 ). These mutations occur quickly to enable rapid adaptation to new environments, and it is hypothesized that secondary selection may act to refine gene expression after the initial burst of adaptation ( Ali and Seshasayee, 2020 ; Rodríguez-Verdugo et al, 2016 ). Thorpe et al, 2017 previously found evidence of positive selection at promoter sites in natural populations of M. tb , suggesting that adaptation in natural as well as experimental populations is facilitated by regulatory mutations.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings have also been obtained in other systems, where experimentally evolved populations have shown adaptation in transcription factors and other global regulators, with global impacts on gene expression (Ali and Seshasayee, 2020;Conrad et al, 2010;Philippe et al, 2007;Rodríguez-Verdugo et al, 2016;Saxer et al, 2014). These mutations occur quickly to enable rapid adaptation to new environments, and it is hypothesized that secondary selection may act to refine gene expression after the initial burst of adaptation (Ali and Seshasayee, 2020;Rodríguez-Verdugo et al, 2016). Thorpe et al previously found evidence of positive selection at promoter sites in natural populations of M. tb, suggesting that adaptation in natural as well as experimental populations is facilitated by regulatory mutations (Thorpe et al, 2017).…”
Section: The Regulatory System As a Target Of Selection In M Tbsupporting
confidence: 87%
“…This reflects general features of M. tb's regulatory network, which exhibits a high degree of connectivity between regulatory pathways (Chauhan et al, 2016;Galagan et al, 2013) as well as a hierarchical structure in which master regulators can rapidly calibrate global patterns of gene expression (Chauhan et al, 2016;Parvati Sai Arun et al, 2018). Similar findings have also been obtained in other systems, where experimentally evolved populations have shown adaptation in transcription factors and other global regulators, with global impacts on gene expression (Ali and Seshasayee, 2020;Conrad et al, 2010;Philippe et al, 2007;Rodríguez-Verdugo et al, 2016;Saxer et al, 2014). These mutations occur quickly to enable rapid adaptation to new environments, and it is hypothesized that secondary selection may act to refine gene expression after the initial burst of adaptation (Ali and Seshasayee, 2020;Rodríguez-Verdugo et al, 2016).…”
Section: The Regulatory System As a Target Of Selection In M Tbsupporting
confidence: 76%
“…Recently, it was shown that in the initial stages of evolution during LTSP, mutations in global regulators confer a higher fitness advantage – an effect that declines over time, leading to local regulators being mutated at a higher frequency later in the experiment [113]. Evidence for, and the role of GASP have also been detected in populations of vector-borne pathogens.…”
Section: Bacterial Growth Dynamics Under Prolonged Nutrient Limitationmentioning
confidence: 99%